CONTRIBUTION OF THE ELP USE ON LEARNING TURKISH AS A FOREIGN LANGUAGE - Burcu Ak Şentürk; Hüseyin Demir (Informascope, 2019)
The study explored the contribution of the European Language Portfolio (ELP) on students' attitudes towards learning Turkish. The study was carried out with 30 foreign students studying at Bartın University the Language Education and Instruction Application and Research Center in the 2018-2019 academic year. The data collection instrument used in this study was semi-structured interviews which were administered to thirty students and an attitude survey designed on a five-point Likert scale with 43 items. The analysis of the interviews indicated that the ELP can boost self-assessment and as a consequence, the students support having more positive attitudes towards learning Turkish.  Additionally, it was declared that the students felt positive towards the ELP. And also according to the results of the questionnaires, they had positive attitudes towards learning Turkish since the purpose of their learning is to survive in Turkey and to pursue their education and career. Furthermore, the findings of the study indicated the students admitted that the ELP was a tool for self-assessment; however since the students were learning Turkish, they sometimes had some problems comprehending the sentences which later turned into an advantage giving them a chance to practice their Turkish.